Invasive carcinoma derived from branch duct-type IPMN may be a more aggressive neoplasm than that derived from main duct-type IPMN - OKABAYASHI, TAKEHIRO (D.A. Spandidos, 2013)
The present study aimed to evaluate the long-term follow-up results of patients with intraductal papillary mucinous neoplasm (IPMN) and to estimate the degree of IPMN malignancy based on pathological and molecular features of resected specimens. The detection rate of IPMN has increased over the last decade; however, the management of this neoplasm remains controversial. This is particularly so for branch duct-type IPMN, which carries a high potential for malignancy and risk of recurrence. We retrospectively reviewed a single institution’s prospective pancreatic resection database to identify IPMN patients who underwent pancreatectomy with curative intent. The clinicopathological variables of 100 patients resected for IPMN were analyzed with a detailed review of histopathological results (borderline lesions, non-invasive carcinoma and invasive carcinoma) to determine the grade of IPMN malignancy based on transforming growth factor (TGF)-β/SMAD4 signaling. The incidence of malignant change was significantly higher in patients with main duct-type IPMN (69.7%) compared with branch duct-type IPMN cases (17.9%). However, patients with an invasive carcinoma had a significantly worse outcome if it was derived from branch duct-type IPMN compared with those derived from main duct-type IPMN, and TGF-β mRNA expression was significantly increased in the former patient group. Immunohistochemistry also showed higher numbers of SMAD4-positive cells in patients with carcinoma derived from branch duct-type IPMN. Our results demonstrated that invasive carcinoma derived from branch duct-type IPMN is more aggressive than that derived from main duct-type IPMN, once invasive morphological change takes place. Determining TGF-β and/or SMAD4 status at initial diagnosis may be useful for stratifying IPMN patients into treatment regimens.